Evaluation of melatonin and AFMK levels in women with breast cancer - de Castro, Tialfi Bergamin [UNESP]; Bordin-Junior, Newton Antônio; de Almeida, Eduardo Alves; de Campos Zuccari, Debora Aparecida Pires [UNESP] (Springer Nature, 2018)
Purpose: Changes in the circadian rhythm may contribute to the development of cancer and are correlated with the high risk of breast cancer (BC) in night workers. Melatonin is a hormone synthesized by the pineal gland at night in the absence of light. Levels of melatonin and the metabolite of oxidative metabolism AFMK (acetyl-N-formyl-5-methoxykynurenamine), are suggested as potential biomarkers of BC risk. The aims of this study were to evaluate levels of melatonin and AFMK in women recently diagnosed with BC, women under adjuvant chemotherapy, and night-shift nurses, and compare them with healthy women to evaluate the relation of these compounds with BC risk. Methods: Blood samples were collected from 47 women with BC, 9 healthy women, 10 healthy night shift nurses, and 6 patients under adjuvant chemotherapy. Compound levels were measured by mass spectrometry. Results and conclusions: Our results showed that women with BC had lower levels of melatonin compared to control group women, and even lower in night-shift nurses and in patients under adjuvant chemotherapy. There was no significant difference of AFMK levels between the groups. In addition to this, high levels of melatonin and AFMK were related to patients with metastasis, and high levels of AFMK were related to the presence of lymph node-positive, tumor > 20 mm and patients who sleep with light at night. Our results showed a reduction of melatonin levels in BC patients, suggesting a relation with the disease, and in addition, point to the importance of melatonin supplementation in women that work at night to reduce the BC risk.
Keywords: AFMK; Blood level; Breast cancer; Circadian rhythmic; Melatonin